Scope of Law in Implementing the Law on Money Laundering in the Framework of Eradication of Criminal Acts of Corruption - Efermin Gulo; Azhali Siregar; Ismaidar Ismaidar (International Journal of Sociology and Law, 2025)
White-collar crime has evolved to a transnational scale, transcending national boundaries. The crimes are increasingly sophisticated and well-organized, making them difficult to detect and eradicate effectively. Criminals continually seek to secure their proceeds through various means, including complex schemes of money laundering involving international financial networks. To enforce the law on money laundering, proof of the occurrence of money laundering is necessary. Therefore, prior to carrying out the investigation, several key elements must be understood, including the basic concepts of money laundering, the methods of money laundering, and indirect methods of evidence. The crime of money laundering is based on Law No. 15 of 2002 and has been carried out in accordance with the applicable provisions, namely Law No. 8 of 1981 concerning the Criminal Procedure Code (KUHAP), and the Procedural Law contained in Law No. 15 of 2002 concerning the Crime of Money Laundering as amended by Law No. 25 of 2003 concerning Amendments to Law No. 15 of 2002 concerning the Crime of Money Laundering. Obstacles that arise in investigating money laundering crimes can be categorized into two categories: legal and non-legal. Legal obstacles include provisions on bank secrecy, investigators' obligations to protect reporters and witnesses, investigators' incomplete perceptions of money laundering, and incomplete information from the Financial Transaction Reports and Analysis Center (PPATK). Non-legal obstacles include reporters not necessarily being victims, limited human resource capacity of investigators, lack of adequate facilities, minimal public awareness, insufficient institutional coordination, and technological gaps that hinder optimal enforcement efforts.